2006
DOI: 10.1128/jvi.01145-06
|View full text |Cite
|
Sign up to set email alerts
|

The NPro Product of Bovine Viral Diarrhea Virus Inhibits DNA Binding by Interferon Regulatory Factor 3 and Targets It for Proteasomal Degradation

Abstract: Bovine viral diarrhea virus (BVDV) is a pestivirus that can establish a persistent infection in the developingfetus and has the ability to disable the production of type I interferon. In this report, we extend our previous observations that BVDV encodes a protein able to specifically block the activity of interferon regulatory factor 3 (IRF-3), a transcription factor essential for interferon promoter activation, by demonstrating that this is a property of the N-terminal protease fragment (NPro) of the BVDV pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
227
3
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 231 publications
(245 citation statements)
references
References 60 publications
13
227
3
2
Order By: Relevance
“…S4A), an IFN antagonist provided in trans cannot rescue the phenotype of this virus. Similar results were also obtained in A549 cells using a different IFN-antagonist protein (BVDV NPro) (25) (Fig. S4B).…”
Section: Resultssupporting
confidence: 76%
“…S4A), an IFN antagonist provided in trans cannot rescue the phenotype of this virus. Similar results were also obtained in A549 cells using a different IFN-antagonist protein (BVDV NPro) (25) (Fig. S4B).…”
Section: Resultssupporting
confidence: 76%
“…The latter were cultured in DMEM with 10% (vol/vol) FCS and supplemental penicillin and streptomycin. To generate control cells expressing the V protein of PIV5 and patient cells expressing functional STAT2, the PIV5 V gene and the full-length ORF of STAT2 were cloned into the bicistronic lentivirus vector (pHR-SIN-CSGW); lentiviruses were produced and the cells were transduced and selected for puromycin resistance as described previously (40). The full-length ORF of human STAT2 was amplified by using specific primers by reverse transcription (Superscript III; Invitrogen) and PCR (HiFi DNA polymerase; Kappa Biosystems), using total RNA from control patient fibroblast cells.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the fact that virus infection prevented Mx induction and at the same time led to the complete disappearance of IRF-3 suggested that the effect of intact virus may be independent of E rns . Previous work has suggested that the effect on IRF-3 of pestiviruses may be mediated through N pro , which targets IRF-3 for proteasomal degradation (Bauhofer et al, 2007;Chen et al, 2007;Hilton et al, 2006; Seago et al, 2007).…”
mentioning
confidence: 99%
“…Moreover, the fact that virus infection prevented Mx induction and at the same time led to the complete disappearance of IRF-3 suggested that the effect of intact virus may be independent of E rns . Previous work has suggested that the effect on IRF-3 of pestiviruses may be mediated through N pro , which targets IRF-3 for proteasomal degradation (Bauhofer et al, 2007;Chen et al, 2007;Hilton et al, 2006; Seago et al, 2007).To assess the functions of the two proteins in the context of intact virus, rather than being expressed as single proteins, we made use of viral mutants lacking either N pro or the RNase activity of E rns (H30F). As shown previously (Schweizer & Peterhans, 2001), Mx (and hence IFN) production induced by extracellular and intracellular dsRNA was completely inhibited in cells infected with wt BVDV (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation